2010
DOI: 10.1038/labinvest.2010.37
|View full text |Cite
|
Sign up to set email alerts
|

Absence of placental growth factor blocks dextran sodium sulfate-induced colonic mucosal angiogenesis, increases mucosal hypoxia and aggravates acute colonic injury

Abstract: Angiogenesis has recently been described as a component of inflammatory bowel disease. Placental growth factor (PlGF), a vascular endothelial growth factor (VEGF) homologue, establishes its angiogenic capacity under pathophysiological conditions. We investigated the function of PlGF in experimental models of acute colitis. Acute colonic damage was induced in PlGF knock-out (-/-) mice and PlGF wild-type (+/+) mice by dextran sodium sulfate (DSS) and trinitrobenzenesulfonic acid (TNBS). The concentrations of PlG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…In an acute colonic injury model, PlGF deficiency impairs mucosal angiogenesis, aggravates epithelial hypoxia, and worsens the disease outcome (Hindryckx et al 2010). Notably, PlGF gene delivery improves healing of the inflamed colon (Hindryckx et al 2010).…”
Section: Colitismentioning
confidence: 99%
“…In an acute colonic injury model, PlGF deficiency impairs mucosal angiogenesis, aggravates epithelial hypoxia, and worsens the disease outcome (Hindryckx et al 2010). Notably, PlGF gene delivery improves healing of the inflamed colon (Hindryckx et al 2010).…”
Section: Colitismentioning
confidence: 99%
“…Dextran sulfate sodium-induced (DSS-induced) colitis is an in vivo model of inflammation where neutrophils are prominent and that is associated with a marked degree of tissue hypoxia (35). Using the acute 6-day time point, we determined the number of neutrophils present in the intestinal mucosa using immunohistochemical staining.…”
Section: Figurementioning
confidence: 99%
“…This is important both to rule out altered neutrophil migration (which was not observed in vitro) but also because, in these whole animal knockouts, PHD3 deficiency of resident cells such as epithelial and endothelial cells could have modified neutrophil influx into the lungs. Murine DSS-induced colitis is also recognized to be profoundly hypoxic (35) and can be characterized histologically by neutrophil-predominant inflammation within the intestinal mucosa, although the specific role neutrophils play in the disease pathogenesis is unclear. In keeping with a reduction in neutrophil-dominant pulmonary inflammation and increased neutrophil apoptosis, we again saw a reduction in neutrophil numbers in the intestinal mucosa of Phd3 -/-animals compared with WT controls.…”
Section: Figurementioning
confidence: 99%
“…Preclinical work has suggested that alternate proangiogenic factors may modulate sensitivity to anti-VEGF-A therapy and allow regrowth of tumor-associated vasculature [11][12][13]. Members of the VEGF signaling family aside from VEGF-A have been implicated in angiogenesis, including placental growth factor (PlGF), VEGF-C, and VEGF-D [14,15]. However, the role of alternate VEGF ligands in angiogenesis remains controversial.…”
Section: Introductionmentioning
confidence: 99%